Planning the training process in Blind football (Sport Science Research, 2025)
The article discusses the basics of planning the educational and training process in Blind football. The purpose of the study is to identify the main problems limiting the effectiveness of planning the educational and training process in football for the blind, as well as to develop a plan for the basic mesocycle of athletes' training. As a result of the analysis of scientific and methodological literature and Internet sources, focus groups and pedagogical observation, it was determined: the number of visually impaired people living in Kazakhstan; The main problems of effective planning of Blind football athletes' sports training have been identified and ranked; a plan for the basic mesocycle of the Blind football training process has been developed; the geography of Blind football development in Kazakhstan has been determined. The novelty of the approach in planning the Blind football training process, taking into account the main problems and the use of methods of foreign coaches, will create the basis for the systematic development of scientific and methodological support for football for the blind in Kazakhstan.
Keywords: Blind football; sports training planning; athletes; educational and training process; basic mesocycle